Factors for success in acquiring information technology - Jawad, Ali Qassim (Cranfield University, 1995)
The acquisition of new IT systems is expensive and risky. Systems often fail to provide the expected services, or may commit an organisation to a particular long-term solution to its information management needs which can be very costly to change. The purpose of this research was to help organisations to manage the IT acquisition process with greater chances of success. In this research `Acquisition of IT' means the whole process of initiating, implementing and then using an information technology system. The approach taken was to identify success factors for IT acquisition. A large number of actual acquisition cases were examined, and a list was compiled of factors reported by people involved in these cases to affect their success or otherwise. The relative importances of these factors were then measured quantitatively by correlating the degree to which each factor was present in the cases, with the degree of success of the cases. This work has produced: a comprehensive list of factors to be considered; a method of defining what is meant by success for a given project; a description of the acquisition project lifecycle; and an identification of the different roles played by different people within an organisation. It is shown how to integrate these considerations into a structured approach to managing IT acquisitions. This integrated approach is called the Success Map. Three mini case studies were included, and one of these was analysed in the light of the findings. In a supplementary section, fifteen guiding principles for people involved in an IT acquisition are presented.